Analysis Collaborative implementation of TRP and Audiolingual methods in learning Chinese vocabulary at Kindergarten A level - Ananda Wahyu Puspa Widuri; Djodjok Soepardjo; Wisma Kurniawati (LP. Ma'arif Janggan Magetan, 2024)
Foreign language learning can shape children's social and cognitive future, Mastery of foreign languages at an early age in education can improve critical thinking, interpersonal skills, and advanced language learning. Chinese is currently the second most spoken language in the world, so it is not surprising that many educational institutions have included Chinese in their curriculum system since early childhood education. The use of TPR (Total Physical Response) and Audiolingual methods is an effective method for learning foreign languages in early childhood. This study used a descriptive qualitative approach. This research involved Chinese language teachers at Filadelfia Kindergarten Surabaya and 15 students at Filadelfia Kindergarten A Surabaya. The results of this study, the use of TPR (Total Physical Response) and Audiolingual methods can improve children's speaking skills and memorize Chinese vocabulary at the Kindergarten A level of Filadelfia Kindergarten Surabaya. The use of collaboration between the TPR method and the Audiolingual Method provides a stimulus for learning Mandarin that is fun for Kindergarten A Filadelfia Surabaya students, this is because the combination of the two methods requires students to be active and make movements in accordance with the vocabulary being taught.